P236 Superior lung function with once-daily QVA149 translates into improvements in patient-reported breathlessness compared with placebo and tiotropium in COPD patients: the BLAZE study. (14th November 2013) - D'Urzo, A; Mahler, DA; Decramer, M; Worth, H; White, T; Alagappan, VKT; Gallagher, N; Chen, H; Kulich, K; Banerji, D
Abstract : Introduction: QVA149, a novel once-daily inhaled dual bronchodilator combining a fixed dose of the long-acting β2 agonist indacaterol and the long-acting muscarinic antagonist glycopyrronium, has demonstrated improvements in dyspnoea versus its mono-components (indacaterol and glycopyrronium), tiotropium, and salmeterol/fluticasone using the interviewer-based Transition Dyspnoea Index (TDI) questionnaire. 1, 2 The BLAZE study evaluated the effect of once-daily QVA149 on patient-reported dyspnoea versus placebo and blinded tiotropium in patients with moderate-to-severe chronic obstructive pulmonary disease (COPD). Methods: This was a 6 week, multicentre, randomised, blinded, double-dummy, placebo-controlled, 3-period, cross-over study. Patients aged ≥40 years with moderate-to-severe COPD, post-bronchodilator forced expiratory volume in 1 second (FEV1 ) ≥30% and <80% of the predicted normal, and post-bronchodilator FEV1 / forced vital capacity <0.7 were randomised to receive QVA149 110/50 μg (via the Breezhaler ® device) or placebo (via the Breezhaler®/ HandiHaler ® device) or blinded tiotropium 18 μg (via the HandiHaler ® device). The primary objective of the study was to evaluate the superiority of QVA149 versus placebo in the improvement of patient-reported dyspnoea as assessed by Self-Administered Computerised (SAC) version of the Baseline Dyspnoea Index (BDI)/TDI after 6 weeks of treatment. Other objectives included; standardised FEV1 area under the curve from 0 to 4 hours post-dose (AUC0–4 h ); rescue medication use; safety and tolerability. Results: Of the 247 patients (mean age 62.8 years) randomised, 191 completed the study. The SAC TDI total score was significantly improved with QVA149 compared with placebo and tiotropium after 6 weeks (figure). FEV1 AUC 0–4 h was significantly higher for QVA149 versus placebo and tiotropium at Day 1 and Week 6 (all p < 0.001). Rescue medication use was significantly lower with QVA149 versus placebo (p < 0.001) and tiotropium (p = 0.002). Incidence rate of adverse events was similar across all the treatment groups (QVA 149: 35.0%; tiotropium: 35.5%; placebo: 39.4%). Conclusion: The BLAZE study provides evidence that the improved lung function with QVA149 translates into greater relief of breathlessness and improved patient-reported outcomes. Reference: Bateman et al . Eur Respir J. 2013 May 30. Vogelmeier et al . Lancet Respir Med. 2013; 1:51–60.